SPECTRUM OF INTRAMEDULLARY SPINAL CORD TUMOURS: CASE SERIES OF 30 PATIENTS - Haq, Naeem Ul; Ali, Mumtaz; Hussain, Ramzan; Khan, Hayat Muhammad (Journal of Postgraduate Medical Institute, 2016)
Objective: To assess the frequency of intramedullary spinal cord tumours based on clinical and histological features. Materials and methods: This descriptive study was performed at the Depart -ment of Neurosurgery Lady Reading Hospital Peshawar, from 20th Jan 2003 to 19th Jan 2009. Treatment charts of patients with spinal tumours were reviewed and patients operated for spinal tumours were identified. A total of 30 pa-tients out of 480 cases of spinal tumours with different intramedullary spinal tumours were considered in this study. Their frequency, clinical features, and histological reports were analyzed in different aspects. Results: There were total of 30 patients with mean age of 36 years and a wide range beginning as young as 6years. Seventeen patients (56%) were male and 13(43%) were female. Common presenting complaints were loss of sensation in 24 patients (80%), paresis in 20 patients (66%), altered sensation in 12 patients (40%), back pain 11 patients (36%) and sphincteric disturbances 9 patients (30%). MRI spine was the main diagnostic tool and was done in 30 (100%) cases. Cervical spine was involved in 12 patients (40%), cervicothoracic 6 patients (20%), thoracic 10 patients (32%), conus 2 patients (08%). Ependy-moma was the most common intramedullary spinal cord tumour 20 patients (60%), while 07 (21%) patients had astrocytoma and 03(09%) had haemangio -blastoma. We had follow up of 1 year with follow up visit after every 3 months. Superficial wound infection in 2 (6.66%) patients, CSF leak in3(10%) cases. Worsening of neurodeficit in 3(10%) patients. Conclusion: Ependymoma and astrocytoma constituted majority of cases. In-tramedullary spinal cord tumours peak during 3rd to 4th decade of life.